Pengembangan Soft Skills Pemuda Riau Menuju Pemuda Dengan Kompetensi Abad 21 - Afrianto Daud; Ando Fahda Aulia; Novitri Novitri; Mirza Hardian; Nita Rimayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This paper describes a community service program conducted by Riau University lecturers which aims to develop several aspects of 21st-century competence through a series of soft skills training for forty participants. This paper further explains the concept of training, the content of the training materials, and the effectiveness of the training. This training lasted for two months with four virtual face-to-face training via Zoom Meetings. The rest was done online through the Google Classroom platform. The content of the training material is divided into two sub soft skills: increasing the ability to take international standard tests (International English Language Testing System/IELTS) and developing public speaking skills. Data from a survey conducted at the end of the program showed that in general, this activity had been running well and effectively. The majority of participants (85.7%) stated that the training activities provided positive benefits for them. More specifically, 63.2% of participants said that their listening skills had improved considerably after the training. Similar data occurs for reading and writing skills (68.4% and 52.6%, respectively). Similar data also appeared in the aspect of public speaking training where the majority of participants admitted that their abilities were getting better after attending the training, especially in terms of engagement with the audience. Thus, this training has benefited the trainees in developing their soft skills.